Game-Based Assessment Tool for Enhancing the Academic Performance of Grade 9 Learners in Araling Panlipunan - Benjamin, Ray Martin; Lopez, Bobby; Santos, Joseline (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study tests the Wordwall game-based assessment tool's effectiveness in enhancing the summative test scores and academic performance of Grade 9 learners in Araling Panlipunan. Additionally, this study developed an action plan for teacher training in integrating the Wordwall application in the classroom, which will contribute to the broader discussion on teacher training and development. Method: The study utilized mixed-method research using a convergent parallel mixed-method design. The study respondents were 40 Grade 9 students for the experimental group, which utilized the assessment tool in the formative assessment, and 40 Grade 9 students for the control group, which used a traditional formative assessment. Thematic analysis was conducted to gather the students' experiences utilizing the Wordwall game-based assessment tool, and an interview with the subject coordinator and perception of the ICT expert was also conducted. Results: Based on the study's findings, the assessment tool developed is content quality assured and technologically accepted. Consequently, the assessment tool effectively enhances the summative test score and academic performance of Grade 9 students in Araling Panlipunan. Novelty: Overall, the study results show a positive effect of using a Game-Based Assessment Tool for enhancing the academic performance of Grade 9 learners. Teachers improve students' performance by using this kind of educational technology in the classroom.